Palmitic Acid, A Critical Metabolite, Aggravates Cellular Senescence Through Reactive Oxygen Species Generation in Kawasaki Disease - Zhu, Qiongjun; Dong, Qianqian; Wang, Xuliang; Xia, Tianhe; Fu, Yu; Wang, Qiaoyu; Wu, Rongzhou; Wu, Tingting (Frontiers in Pharmacology, 2022)
Coronary artery lesions (CALs) are severe complications of Kawasaki disease (KD), resulting in stenosis and thrombogenesis. Metabolomic profiling of patients' plasma could assist in elucidating the pathogenesis of CALs and identifying diagnostic biomarkers, which are imperative for clinical treatment. The metabolic profiles between KD patients with CALs and without CALs (non-coronary artery lesion, or NCAL, group) indicated the most significantly differentially expressed metabolite, palmitic acid (PA), showed the most massive fold change at 9.879. Furthermore, PA was proven to aggravate endothelial cellular senescence by increasing the generation of reactive oxygen species (ROS) in KD, and those two phenotypes were confirmed to be enriched among the differentially expressed genes between KD and normal samples from GEO datasets. Collectively, our findings indicate that cellular senescence may be one of the mechanisms of vascular endothelial damage in KD. PA may be a biomarker and potential therapeutic target for predicting the occurrence of CALs in KD patients. All things considered, our findings confirm that plasma metabolomics was able to identify promising biomarkers and potential pathogenesis mechanisms in KD. To conclude, Palmitic acid could be a novel target in future studies of CALs in patients with KD.